Pelaksanaan Uji Kompetensi Keahlian Teknik Komputer dan Jaringan di SMK Negeri 1 Cempaga dalam Mempersiapkan Lulusan yang Siap Kerja - Dwi Wahyu Prabowo; Nurahman; Eka Prasetyaningrum; Istanta; Wenti Utari (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The Competency Certification Examination (UKK) at SMK Negeri 1 Cempaga was conducted as a strategic response to the need for vocational school graduates to meet the demands of the industry. Given the gap between school-based learning and real-world expectations, this community service initiative aimed to bridge that divide by strengthening students’ practical readiness through a structured certification process. Specifically, the UKK assesses students' skills in Computer and Network Engineering. The implementation of the UKK follows several stages, including preparation and coordination, exam package selection, pre-UKK simulation, examination execution, and evaluation with follow-up actions. The preparation phase involved collaboration between the school and Universitas Darwan Ali to ensure a smooth process. The pre-UKK simulation plays a crucial role in providing students with practical experience prior to the actual exam. The UKK was conducted with the involvement of external assessors from Universitas Darwan Ali, who objectively evaluated the students' competencies. The evaluation results indicated that most of the participants successfully completed the tasks according to industry standards. However, a challenge arose due to the limited preparation time, as the UKK was scheduled only a month after the completion of the Industrial Work Practice (PKL). Consequently, recommendations for improvements were made to optimize the UKK implementation in the following years. Overall, the UKK activity provided valuable experience for students and served as a benchmark for their readiness to enter the workforce